Digitalisasi Toko Kelontong Melalui Program Ayo SRC dalam Perspektif Ekonomi Islam: Studi Kasus Toko SRC (Sampurna Retail Community) Kecamatan Paciran - Shofiyah; Nafilah Shobibatur Rohmah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2024)
This research aims to describe the management of the utilization of the Ayo SRC program application at SRC shops in Paciran sub-district as well as management and utilization from an Islamic Economics perspective. This research uses qualitative descriptive research with a case study type. Data collection was carried out using interviews, observation and documentation methods. To prove the validity of the data using triangulation. The data sources and analysis techniques used are data reduction steps, data presentation and drawing conclusions. The research results show that the management of the use of the Ayo SRC program application is in accordance with the management of retail store management, including the strategy for setting prices and store profits. The SRC shop is also digitizing so that it can keep up with current developments in various aspects. From an Islamic perspective, it is also in accordance with Islamic principles by not committing acts of maisir, gharar, dzalim, iktikar, usury. Meanwhile, the contract used in the MY AYO application uses a greeting contract, namely the buyer pays first and then the goods will be delivered by the seller to the consumers.